1993
DOI: 10.1128/iai.61.9.3636-3641.1993
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the stage-specific 82-kilodalton adhesion molecule of Trypanosoma cruzi metacyclic trypomastigotes in host cell invasion

Abstract: This study provides several pieces of evidence indicating that 3F6-Ag, identified by monoclonal antibody (MAb) 3F6 as a stage-specific glycoprotein of approximately 82 kDa on the surface of metacyclic trypomastigotes of different Trypanosoma cruzi strains, promotes the entry of parasites into host cells through a ligand-receptor type interaction. First, invasion of Vero cells by metacyclic trypomastigotes of both CL and Tulahuen strains was significantly inhibited by MAb 3F6 or its Fab fragments. Second, purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
9

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(47 citation statements)
references
References 25 publications
4
34
0
9
Order By: Relevance
“…Instead of the 75 kDa polypeptide, Vero cells transfected with pc-gp82+SP and treated with tunicamycin expressed a 70 kDa species that may correspond to the 70 kDa polypeptide obtained by digestion of gp82 with either PNGase F or endo H (not shown). This result is similar to that obtained with metacyclic trypomastigotes treated with tunicamycin (Ramirez et al 1993). In the same manner as the cells treated with PNGase F, no change was detected in the profile of polypeptides synthesized by Vero cells transfected with pc-gp82 after treatment with tunicamycin.…”
Section: Expression Of T Cruzi Gp82 Protein In Vero Cells To Ex-supporting
confidence: 88%
See 2 more Smart Citations
“…Instead of the 75 kDa polypeptide, Vero cells transfected with pc-gp82+SP and treated with tunicamycin expressed a 70 kDa species that may correspond to the 70 kDa polypeptide obtained by digestion of gp82 with either PNGase F or endo H (not shown). This result is similar to that obtained with metacyclic trypomastigotes treated with tunicamycin (Ramirez et al 1993). In the same manner as the cells treated with PNGase F, no change was detected in the profile of polypeptides synthesized by Vero cells transfected with pc-gp82 after treatment with tunicamycin.…”
Section: Expression Of T Cruzi Gp82 Protein In Vero Cells To Ex-supporting
confidence: 88%
“…gp82 is a surface glycoprotein which contains N-linked oligosaccharide side chains and anchored to the mem-brane through a glycosylphosphatidylinositol moiety (Araya et al 1994;Cardoso de Almeida, and Heise 1993;Ramirez et al 1998). The cDNA clone 518 encodes a polypeptide of 516 amino acids with a molecular mass of 55.6 kDa, which may correspond to the precursor of gp82 devoid of N-linked oligosaccharides (Araya et al 1994;Ramirez et al 1993). The structure of gp82 predicted from the deduced amino acid sequence is very unusual for a membrane protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a multifactorial process where plasma membrane components from the parasite and host cell seem to be involved in ligand-receptor interactions. Some authors have suggested that the TCT and META invasion processes are different, because each stage uses their own set of molecules to adhere and invade the host cell (Ramirez, Ruiz Rde, Araya, Da Silveira, & Yoshida, 1993). We have described that MVs from META-THP-1 interaction avoid complement lysis and increase the invasion of eukaryotic cells by META forms (Cestari et al, 2012).…”
Section: Infective Forms Of T Cruzi Induce Microvesicles To Invadementioning
confidence: 99%
“…A clonagem de um membro dessa família (Tc85-ll) revelou sua capacidade de adesão a células de mamíferos e a laminina (Giordano et al, 1994(Giordano et al, e 1999. Outros laboratórios também implicaram moléculas de aproximadamente 85 kDa na interação do parasita com a célula do hospedeiro (Boschetti et al, 1987;Lima et al, 1989;Ramirez et al, 1993e Araguth et al, 1988 incluindo uma proteína de 85 kDa, provavelmente da mesma superfamília, mas diferente da Tc85-l l, descrita como receptor de fibronectina ( Ouaissi et al, 1986). Anticorpos contra moléculas de mesma massa molecular inibiram a internação do parasita (Araguth et al, 1988).…”
Section: Discussionunclassified